Using the Python Lightkurve Module to Analyse Light Curves for Beginners - Putra, Singgih Prana (University of Muhammadiyah Sumatera Utara, 2023)
A binary star is a star system that has been studied by astronomers around the world since the 17th century. From the beginning, binary star research used simple methods and tools. However, since the 20th century, computers and programming languages such as Python have been used to study binary stars and their light curves. The development of the Lightcurve Python module is very helpful for people and ordinary people to understand how to use the Lightcurve Analyser in an easy to understand language. There are many tutorials on how to use the Python light curve module on Youtube channels, which can be used for references such as Planet Hunters